Manajemen Perubahan, Keterlibatan Kerja, dan Motivasi Kerja terhadap Kinerja Pegawai Kecamatan - Astuti, Yuniar; Firdaus, Vera; Andriani, Dewi (Universitas Proklamasi 45, 2025)
Optimizing the performance of sub-district employees relates to their ability to adapt to change. This research aims to determine how Change Management, Work Involvement, and Work Motivation influence employee performance in Sidoarjo. The study uses a quantitative method. It draws on a sample of 90 respondents, selected by cluster sampling. Data was collected using a questionnaire. Data analysis used SPSS Version 25 to test hypotheses and applied multiple linear regression. Results show that Change Management has a positive, significant effect on Employee Performance. Job Involvement also has a positive, significant impact. However, Work Motivation does not affect Employee Performance. The study finds that Change Management, Job Involvement, and Work Motivation together significantly influence employee performance.